2011
DOI: 10.3892/etm.2011.413
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of keratins 8, 18 and 19 influences invasiveness of human cultured squamous cell carcinoma and adenocarcinoma cells

Abstract: Abstract. Keratin (K) expression index has been reported to be related to cell invasion activity in adenocarcinoma. In a previous study, we observed a negative correlation between K expression and cell invasion activity; i.e., when many Ks are expressed in the cells, the cell activity is low. To further elucidate the correlation between Ks and invasion activity, RNA interference experiments of K8, K18 and K19 were carried out to clarify the essential role of Ks using T24 and HEC-1 as typical squamous cell carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Originally thought to be mechanical scaffolds that maintain the structural and mechanical integrity of cells and tissues, IFs were later found to participate in many important physiological functions, such as distribution of organelles, signal transduction, cell polarity and gene regulation [1][2][3][4]. Changes in IF expression have been correlated with various diseases, including cancer progression and acquisition of a metastatic phenotype [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Originally thought to be mechanical scaffolds that maintain the structural and mechanical integrity of cells and tissues, IFs were later found to participate in many important physiological functions, such as distribution of organelles, signal transduction, cell polarity and gene regulation [1][2][3][4]. Changes in IF expression have been correlated with various diseases, including cancer progression and acquisition of a metastatic phenotype [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The same trends were observed by Bakke-McKellep, et al 21 in Atlantic Salmon. The action of SBA on apoptosis and autophagic death is mediated by reactive oxygen species (ROS) generation in the same cell line 22,23 . SBA initiates cell apoptosis and declines the expression of mRNA of Bcl-2 (proteins that regulate cell death) in IPEC-J2 12 .…”
Section: Sba Induced Cell Apoptosis By Down Regulating the Expression...mentioning
confidence: 99%
“…Related studies have shown that the expression of cytoskeleton proteins (KRT8, KRT18 and ACTA) is closely related to a variety of cell life activities. For example, KRT8 and KRT18 acts a crucial role in regulating the response of cells to apoptosis 23,28 . Absence or mutation of KRT8 or KRT18 renders hepatocytes markedly susceptible to apoptosis.…”
Section: Sba Induced Cell Apoptosis By Down Regulating the Expression...mentioning
confidence: 99%
See 1 more Smart Citation
“…Then, many researches indicated that keratins played a very important role in growth process of hair, for example, keratin 17 and tumor necrosis factor-α could regulate growth cycle of hair [4]; keratin 2-keratin 5 were involved in growth process of hair [5]. In addition, some keratins were also related to the function of epithelial cells, for example, keratin 8 and keratin 18 could guarantee rigidity and structure integrity of extracellular matrix of epithelial cells, affect intracellular transportation mechanism and signaling pathway, and might inhibit the apoptosis of epithelial cells [68]; keratin 8 could play a role in infection activity of transferable cells of epithelium [9]. In addition, keratins also had other important function on cells, for example, keratin 18 played a significant role in estrogen receptor α signaling pathway regulation [10]; keratin 23 could regulate functional status of 14-3-3ε scaffolding protein in cytoplasm, and then regulate signal transduction, cell cycle, cell apoptosis and other processes [11].…”
Section: Introductionmentioning
confidence: 99%